The immune NIK1/RPL10/LIMYB signaling module regulates photosynthesis and translation under biotic and abiotic stresses. - Marco Aurélio Ferreira; Ruan M. Teixeira; Otávio J. B. Brustolini; Thainá F. F. Saia; James Jean-Baptiste; Nathalia G. A. Ribeiro; Sâmera S. Breves; Fellipe R. Sampaio; Eulálio G. D. Santos; Borys A. Leon; Celio C. Oliveira; Christiane E. M. Duarte; et al. (Nature Communications)
Abstract Photosynthesis and translation are targets of metabolic control and development in plants, yet how stress signals coordinately regulate these opposing energy-producing and consuming processes remains enigmatic. Here, we unravel a growth control circuit that ties photosynthesis to translational control in response to biotic and abiotic signals. Our findings reveal that the L10-INTERACTING MYB DOMAIN-CONTAINING PROTEIN (LIMYB), a key player of the NUCLEAR SHUTTLE PROTEIN-INTERACTING KINASE 1 (NIK1)/ RIBOSOMAL PROTEIN L10 (RPL10) antiviral signaling pathway, not only downregulates translation genes, but also represses photosynthesis-related genes and photosynthesis itself. LIMYB repressor activity, regulated by phosphorylation, is crucial for the decline in photosynthesis under stress. NIK1 activation by PAMPs or the phosphomimetic NIK1-T474D represses photosynthesis-related genes and photosynthesis in control but not in limyb lines. Furthermore, heat and osmotic stress also activate the NIK1/RPL10/LIMYB signaling circuit in wild type. These stresses induce NIK1 phosphorylation, but not marker gene repression, in limyb, indicating that LIMYB connects NIK1 activation to stress-mediated downregulation of translation- and photosynthesis-related genes. This coordinated repression via the NIK1/RPL10/LIMYB module may help plants adapt to changing environments.